2008
DOI: 10.1089/jwh.2007.0677
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Vulvodynia Symptoms in a Sample of U.S. Women: A Follow-up National Incidence Survey

Abstract: Objective: To estimate the annual incidence of vulvodynia-like symptoms and evaluate triggers of vulvar pain in a sample of U.S. women. Methods: After a 1-year interval, women who previously participated in a national vulvodynia prevalence study were recontacted and administered a telephone questionnaire that assessed self-reported vulvodynia-like symptoms and triggers of symptoms. Results: From the original cohort of 425 women, 285 (67%) participated in this follow-up study. Symptoms consistent with vulvodyni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…7 Nguyen et al questioned women with screened and verified vulvodynia about periods in the past in which vulvar pain resolved (remission) and reported an overall remission rate of 33.0% (46/138). 26 However, by design, all women in their study had vulvar pain consistent with vulvodynia and hence all with a remission had subsequently relapsed, whereby those without a relapse would not have been within their study population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…7 Nguyen et al questioned women with screened and verified vulvodynia about periods in the past in which vulvar pain resolved (remission) and reported an overall remission rate of 33.0% (46/138). 26 However, by design, all women in their study had vulvar pain consistent with vulvodynia and hence all with a remission had subsequently relapsed, whereby those without a relapse would not have been within their study population.…”
Section: Discussionmentioning
confidence: 99%
“…6 Similarly, in a nationwide population-based study, Sutton et al found that 37 of 72 women meeting criteria for vulvodynia at their baseline survey denied ever having had these symptoms when asked a year later (51.4%). 7 We considered women with symptoms that resolved to have remitted in our analysis-even when they reported no previous symptoms, while Sutton et al excluded these women from their analysis, thereby explaining the lower remission rate (31.4%) they reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Pain presentation varies and may be described as spontaneous, provoked by stimulation (i.e., intercourse or tampon use), or both. 1,3 While some studies have documented that women with vulvodynia report a poor quality of life 4,5 and suffer from psychological distress manifested as anxiety and depression, [6][7][8][9][10] evidence of an association between vulvodynia and mental health outcomes remains limited.…”
Section: Introductionmentioning
confidence: 99%